Plankton and dissolved nutrient data from 2016 mesocosm experiment manipulating Si:N and copepod grazing on Baltic Sea plankton community - Kriste Makareviciute-Fichtner; Birte Matthiessen; Heike K Lotze; Ulrich Sommer (PANGAEA, 2020)
Phytoplankton, microzooplankton, copepod and dissolved nutrient data from a mesocosm experiment, which took place in summer 2016. A range of Si:N ratios and two levels of copepod grazing pressure were manipulated on a natural plankton community in Kiel Bay, Southern Baltic Sea, Germany.